Star trek. Into darkness [videorecording (Blu-Ray)] - Abrams, J. J. (Jeffrey Jacob), 1966-; Abrams, J. J. (Jeffrey Jacob), 1966-; Pine, Chris, 1980-; Quinto, Zachary; Saldana, Zoë, 1978- (Paramount, 2021)
Captain Kirk leads his crew on a journey to a war-zone world to capture a one man weapon of mass destruction.